Analisis Kedudukan Hukum Perjanjian Pihak Label Musik Dan Komposer Dengan Sistem Jual Beli Putus - Prawiranegara, Lalu Mohamad Arief; Kurniawan (Departement Business Law, Faculty of Law, University of Mataram, 2024)
This research purpose is to analyze the legal position of agreements between music labels and composers using sold flat agreement systems and analyze the regulation after the Constitutional Court decision Number 63/PU/XIX/2021. This type of research is a normative legal research method that originates from the regulations of Act Number 28 of 2014 concerning Copyright. The legal validity of the agreement between the music label and the composer in the sold flat agreement systems before the enactment of Act Number 28 of 2014 concerning Copyright that is, legally and formally null and void, because creations in Article 18 of Act Number 28 of 2014 are the object of the agreement and are prohibited from being sold by Sold flat system. The economic rights of the creator in this case the composer automatically returns to the creator. Regulation of agreements between music labels and composers under the Constitutional Court decision Number 63/PU/XIX/2021 that the judicial review submitted by Musica Studios is final so that Article 18 and Article 30 of Act Number 28 of 2014 concerning Copyright do not contradict with the 1945 Constitution. Act Number 28 of 2014 restores fundamental rights owned by the creator, the fundamental rights owned by creators both moral rights and economic rights and the composer can still make an agreement with the Music Label regarding the rights to use the work for commercialization, with the implication that the creator/composer will still receive royalties as long as the work is commercialized.